Co-creating sensible care plans using shared decision making: Patients' reflections and observations of encounters. Issue 6 (June 2022) - Kunneman, Marleen; Hargraves, Ian G.; Sivly, Angela L.; Branda, Megan E.; LaVecchia, Christina M.; Labrie, Nanon H.M.; Brand-McCarthy, Sarah; Montori, Victor
Highlights: In shared decision making (SDM) patients and clinicians co-create care plans. SDM research rarely focuses on how much sense the care plan makes to patients. We compared sensibility of care plans in usual care and when using an SDM tool. Plan sensibility was high in both arms and not related to treatment adherence. Plans made sense to patients given their know efficacy, safety, and implementation. Abstract: Objective: To evaluate how the use of a within-encounter SDM tool (compared to usual care in a randomized trial) contributes to care plans that make sense to patients with atrial fibrillation considering anticoagulation. Methods: In a planned subgroup of the trial, 123 patients rated post-encounter how much sense their decided-upon care plan made to them and explained why. We explored how sense ratings related to observed patient involvement (OPTION12), patient's decisional conflict, and adherence to their plan based on pharmacy records. We analyzed patient motives using Burke's pentad. Results: Plan sensibility was similarly high in both arms (Usual care n = 62: mean 9.4/10 (SD 1.0) vs SDM tool n = 61: 9.2/10 (SD 1.5); p = .8), significantly and weakly correlated to decisional conflict (rho = −0.28, p = .002), but not to OPTION12 or adherence. Plans made sense to most patients given their known efficacy, safety and what is involved in implementing them. Conclusion: Adding an effective intervention to promote SDM did not affect how much, or why, care plans made sense to patients receiving usual care, nor patient adherence to them. Practice Implications: Evaluating the extent to which care plans make sense can improve SDM assessments, particularly when SDM extends beyond selecting from a menu of options.